Assessment of oligometastasis status of prostate cancer following combined robot-assisted radical prostatectomy and androgen deprivation versus androgen deprivation therapy alone using PSA percentage decline rate - Li, Xuwen; Xi, Haibo; Cheng, Xiaofeng; Yu, Yue; Zhang, Cheng; Wang, Gongxian; Zhou, Xiaochen (Frontiers in Endocrinology, 2023)
Objective: To compare the tumor control in prostate cancer patients with oligo-metastasis following combined robot-assisted radical prostatectomy and androgen deprivation versus androgen deprivation therapy alone based on total prostate-specific antigen (tPSA) assessment. Methods: Medical data of a total of 18 prostate cancer patients with oligometastasis administered in The First Affiliated Hospital of Nanchang University from March 2017 to March 2018 were prospectively collected. 10 patients received a combined therapy of robot-assisted radical prostatectomy and pharmaceutical androgen deprivation (RARP+ADT group), while 8 patients received pharmaceutical androgen deprivation therapy alone (ADT group). Then demographic characteristics, prostate volume, tumor characteristics and tPSA data were analysised and compared. Statistical analysis was performed using t-test for continuous variables and Pearson chi-square test or Fisher’s exact test for categorical variables. Results: No significant difference was found in patients’ age (p = 0.075), prostate volume (p = 0.134) and number of bone metastasis (p = 0.342). Pre-treatment Gleason score was significantly lower in RA group (p = 0.003). Patients in RARP+ADT group had significantly lower pre-treatment tPSA (p = 0.014), while no statistical difference was noted in reexamined tPSA (p = 0.140) on follow-up. No statistical difference was noted in tPSA decline rates (declined tPSA value per day) in RARP+ADT and ADT group (8.1 ± 4.7 verse 7.5 ± 8.0 ng/ml/d, p = 0.853). However, tPSA percentage decline rate (declined tPSA percentage per day) was significantly higher in RARP+ADT group (11.6 ± 1.5 %/d verses 2.9 ± 2.2 %/d, p < 0.001). Immediate urinary continence was achieved in 9 patients (90 %) upon removal of urethral catheter on post-operative day 7 in RARP+ADT group. Conclusion: ADT alone and in combination with RARP both provide effective tumor control in patients suffering from prostate cancer with oligometastasis. ADT combined with RARP exhibited significant advantage in PSA percentage decline rate without compromising patients’ urinary continence. Long-term tumor control requires further follow-up.